Komparasi Metode Titrimetri Dengan Spektrofotometri UV-Vis pada Analisis Chemical Oxygen Demand (COD) Output IPAL Domestik Berdasarkan Linieritas, Akurasi dan Presisi: Comparison Of Titrimetric With UV-Vis Spectrophotometry Methods For The Analysis Of Chemical Oxygen Demand (COD) Output Domestic IPAL Based On Linierity, Accuracy and Precision - Ida Lestari; Peni Pujiastuti; Yari Mukti Wibowo (LPPM Universitas Mataram, 2023)
The method of a test must be evaluated and tested to ensure that the method is capable of producing valid data. So that validation needs to be done as a quality control that provides assurance that the measurements and results obtained are reliable. This study aims to determine the value and comparison of the values of linearity, accuracy, and precision of the titrimetric and spectrophotometric methods in COD analysis. Determination of the COD value for the titrimetric method was carried out by redox titration using a solution of Ferro Ammonium Sulphate (FAS). While the spectrophotometric method was carried out using UV-Vis spectrophotometry at a wavelength of 420 nm. The research results obtained a linear regression value for the titrimetric method of 0.9989, while the spectrophotometric method was 0.9991, this indicates that the linear regression value of the spectrophotometric method is better than the titrimetric method. The results of the accuracy analysis for the titrimetric method obtained a value of 111.48%, while for the spectrophotometric method it was 103.11%, this shows that the accuracy value of the spectrophotometric method is better than the titrimetric method. The precision analysis results for the titrimetric method obtained a value of 1.77%, while for the spectrophotometric method it was 1.55%, this shows that the spectrophotometric method has a better precision value than the titrimetric method. Based on the comparison of the results of statistical validation using the T-test, there was no significant difference in data between the titrimetric method and the spectrophotometric method.